Interpersonal relationship communication training according to Peplau theory improves nursing team cooperation in the operating room of Haji Hospital, East Java Province, Surabaya - Yuswanto, Tri Johan Agus; Andriani, Wahyu; Sepdianto, Tri Cahyo; Anjaswarni, Tri (Jurnal Keperawatan, 2024)
Introduction: Interpersonal communication is a competency that must be possessed to foster cooperation. Failure in communication will reduce cooperation, which will impact the quality of service, especially in the operating room. Objectives: The aim of this research is to prove the effect of interpersonal relationship communication training according to Peplau's theory on nursing team collaboration in the operating room of the Haji Hospital, East Java Province. Methods: The quasi-experimental research method uses a pre-test-post-test control group design. The independent variable is interpersonal communication training. The dependent variable is the collaboration of the nursing team in the operating room. Data analysis using Wilcoxon and Mann-Whitney tests. The sample consisted of 25 nurses, with 13 in the treatment group and 12 in the control group. Results: The results of the Wilcoxon signed rank test for the treatment group were p = 0.002 ≤  = 0.05. There was a significant difference between the pre-test and post-test results in the treatment group. In the control group, the Wilcoxon test obtained p = 1.00 ≥  = 0.05, meaning there was no difference between the pre-test and post-test results. In the Mann-Whitney U test post-test for the treatment and control groups, the p value was 0.004 ≤ = 0.05, indicating that there is an influence of interpersonal relationship communication training on nursing team collaboration. Conclusion: Nurses' interpersonal communication in the operating room is very important to improve teamwork. Nurses are expected to improve interpersonal communication and teamwork.